One-pot synthesis and biological evaluation of N-fused imidazoles as antibacterial agents and bacterial topoisomerase inhibitors - Eleanor P. Bentley; Oriole W. Song; Ira Glassman; Leepakshi Johar; Cheldon A. Alcantara; Veronica L. Show; Adam R. Johnson; Hendrik Szurmant; David A. Vosburg (Results in Chemistry)
A series of N-fused imidazoles related to known inhibitors of human topoisomerase IIα were rapidly synthesized by a multicomponent GBB reaction under environmentally friendly conditions with microwave heating. Two of the compounds synthesized exhibited bacteriostatic activity against methicillin-resistant Staphylococcus aureus (MRSA) and other gram-positive bacteria, but none showed significant inhibition of bacterial topoisomerase.